PENGELOLAAN ACARA “BANDUNG LAUTAN SEPEDA” OLEH BIRO HUMAS DAN PROTOKOL SEKRETARIAT DAERAH PROVINSI JAWA BARAT - Putri Meysha Nabila Fauzziya; Aat Ruchiat Nugraha (Institute of Research and Community Outreach - Petra Christian University, 2020)
One of the characteristics of the success of public services carried out by an organization is in the form of delivering information and organizing an activity that is beneficial to stakeholders. Submitting information and organizing these activities is part of public communication that must be carried out by the public relations department of an organization. Is done by the Public Relations and Protocol Bureau of the Regional Secretariat of West Java Province which has the function as the front guard to provide information through various media publications with a deliberate strategy. The form of undertaken strategy is public relations events and media relations which packaged in activities with the theme